Design and development of an integrated enset processing machine suitable for central highland farmers of west shewa zone Ethiopia - Beka Adugna Jima; Kishor Purushottam Kolhe; Moera Gutu Jiru (Discover Agriculture)
Abstract The development of Integrated Enset processing technology is significant for the easy availability of stable food in the current condition for fulfilling the pangs of hunger in Ethiopia, currently; individual manual technologies such as decortication, corm granting, bulla extraction, and fermenting techniques eventually contribute to utilizing food security such as Kocho, which is not affordable for the marginal farmers of Ethiopia. However, there is a lack of integrated compromise of the all-function process of corm granting, decortication, and pulverization in one machine wholesome of the product such as Kocho, and bulla within consuming time and labor. Therefore, it is decided to design and develop an integrated enset processing machine for central high land of Ethiopian farmers with high-quality production. The physical and mechanical properties of the enset is studied to get an efficient and robust design of the various components. The overall design and development of proposed machine components were carried out at Adama Science and Technology University, Ethiopia by using ANSYS 2023 R1 software by considering the engineering economics and material specifications as per ASTM standards. The process parameters of the proposed machine are identified as feed rate, drum speed, concave to drum clearance, power requirement, etc. Also, the enset characteristics were considered as decorticating and granting, fiber cutting resistance, fiber length, dimension, shape, and weight. The overall developed enset integrated machine assembles are analyzed for granting and decorticating with drum clearance and bulla extraction throughput capacity, reliability, simplicity, safety, and overall cost. The machine's safety from a Design Perspective is checked and validated by a simulation study on the critical parts subjected to higher stresses. The cost of available individual decorticators, granting, pulverized, and bulla squeezer machines is costly to the farmer’s community. Therefore; the proposed Integrated enset machine will be handy to the marginal and low-cost enset-producing farmers of West Shewa Zone Ethiopia.